IMPLEMENTATION OF INNOVATIVE ENTREPRENEURSHIP INTO PRACTICE - Kuchkarova Gulrukh Mukhtarbekovna (Ecomind Press, 2025)
This article analyzes the processes of implementing innovative entrepreneurship into practice and its significance in economic development. It highlights the opportunities of commercializing new ideas, developing start-up projects and creating competitive products and services through innovative entrepreneurship. Based on international experience, the paper also discusses the main directions of developing innovative entrepreneurship in Uzbekistan and provides practical recommendations for its effective application.
Keywords: Innovative entrepreneurship, practice, start-up, commercialization, innovative products, competitiveness.